Código de Ética Profissional do Servidor Público e o ato ético de servir: avaliação do nível de conhecimento no âmbito da UFC com o servidor docente e o técnico-administrativo - Marques, Regina dos Santos (2012)
The theme is ethics from philosophical studies originated in the ancient world, matured and discussed the Middle Ages, Modern and Contemporary World. His concepts and principles have been discussed far beyond the academy, in the professional field, when it comes to ethics in organizations. The ethics is present in the Code of Professional Ethics (CEP) as well as the Legal Regime Single of federal public servants and need for ongoing discussion. Being composed of professional ethics ethical principles and moral values enshrined in the code of ethics of the server, it is necessary to their knowledge and understanding to exercise everyday. Both ethical and moral values acquired based on the cultural construction of each professional category, it fails to bring the "fore" the precepts that underlie Socratics. Ethics for Socrates was the interior refinement. Faced with this question, one has the general objective to assess the level of knowledge of servers teachers and technical and administrative staff of the Federal University of Ceará on the Code of Ethics Public, embodied in Decree No. 1171 of 1994 and No. 6029, 2007 in art. 116 and 117 of Law No. 8112 of 1990 and in art. 37, main clause of the Federal Constitution of 1988. The methodology consisted of a literature review because it involves explanations grounded in books, magazines, articles and white papers that address the issue in question; application of a questionnaire among the servers taken at random from the population surveyed in the period from March to May, 2012, 13 units manning the UFC. It is concluded that more than half of respondents said they do not know the Code of Professional Ethics Server; servers consider important the promotion of professional ethics within the Federal University of Ceará. Because of this, it is understood that there is need to implement actions, such as courses, seminars, lectures, and other promotions aimed at promoting professional ethics in the Federal University of Ceará.